MANAJEMEN OPERASIONAL PENDIDIKAN MASA PANDEMI COVID 19 DI RA PERWANIDA WONOSOBO - Laily Mardiyati; Imron Imron (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The increasingly widespread spread of COVID-19 requires that learning in schools becarried out online. The problem that has arisen due to Covid-19 is the operational costs ofschools, this also occurs at RA PERWANIDA WONONOSOBO, as a private educationalinstitution. They rely on fees from their parents for school operational costs. When manyparents stop working or their income drops, it is possible that they do not pay tuition feesto school. In a situation like this, schools don't get income so they can't afford teachers'salaries, this becomes a big problem.This research is a qualitative research. Collecting data using interview, observation anddocumentation methods. Test the validity of the data using triangulation techniques. Dataanalysis used a description technique with the Miles and Huberman interaction analysismodel with the flow including data collection, data reduction, and data presentation.With that, the head of RA PERWANIDA WONOSOBO builds cooperation with severalguardians of students to meet the salaries of teachers and employees, includingcollaborating with several guardians of students who will later use the sales proceeds forcapital and part of the income for school operational costs, as well as cooperation withothers, this is done to fulfillment of school operational costs.